Edukasi Dan Pendampingan Pembuatan NIB Untuk UMKM di Kelurahan Medokan Ayu Kota Surabaya - Dinata, Aldo Prayoga; Taufiq, M.; Wijaya, Riko Setya (Peneliti.net, 2023)
At this time the Medokan ayu Village is experiencing an increase in the number of .MSMEs This is because more and more people want to open their own businesses due to the Covid-19 pandemic, where many employees have been laid off by companies, it is difficult to find new jobs, and other problems. However, with the development of MSMEs.In the Medokan Ayu sub-district, many MSMEs still do not know how important business legality is. The development of MSMEs actors requires permits and legality to show that their business is feasible and is operating. The preparation stage is where we collect data and map MSMEs in the Medokan Ayu village. Then the Implementation and Education Stage, we made socialization of business legality for MSMEs in the Medokan Ayu Village. Next was the manufacturing stage where we opened an NIB post during socialization, in several RWs in the Medokan Ayu sub-district, and door to door. Our first activity carried out outreach in the Medokan Ayu Sub-district where we also opened an NIB post there. In the second activity, we opened NIB posts in several RWs in the Medokan Ayu sub-district. our third activity is going door to door to MSMEshouses that need NIB. Conclusion: Making a Business Identification Number (NIB) is intended so that MSMEs actors in the Medokan Ayu Village can have business legality. Suggestions It is hoped that Medokan Ayu Village will continue to provide education to MSMEs that Legality is important for them. And it is also hoped that the Medokan Ayu Village for MSMEs will make it easier for the service of procedures for managing NIB.